2016
DOI: 10.1093/eurheartj/ehw022
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cardiac dysfunction during adjuvant breast cancer therapy (PRADA): a 2 × 2 factorial, randomized, placebo-controlled, double-blind clinical trial of candesartan and metoprolol

Abstract: AimsContemporary adjuvant treatment for early breast cancer is associated with improved survival but at the cost of increased risk of cardiotoxicity and cardiac dysfunction. We tested the hypothesis that concomitant therapy with the angiotensin receptor blocker candesartan or the β-blocker metoprolol will alleviate the decline in left ventricular ejection fraction (LVEF) associated with adjuvant, anthracycline-containing regimens with or without trastuzumab and radiation.Methods and resultsIn a 2 × 2 factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
430
5
41

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(482 citation statements)
references
References 32 publications
6
430
5
41
Order By: Relevance
“…The PRADA (Prevention of Cardiac Dysfunction During Adjuvant Breast Cancer Therapy) trial tested whether angiotensin receptor blockers and/or beta‐blockers would be effective in preventing cardiotoxicity in patients diagnosed with breast cancer receiving anthracycline‐based chemotherapy with and without trastuzumab. The study showed modest benefit of candesartan, but not metoprolol, in preventing LVEF reduction assessed by magnetic resonance imaging94; however, neither medication was effective in preventing increases in high‐sensitivity troponin, a marker of subclinical myocardinal injury. A more‐recent randomized controlled trial failed to reproduce such beneficial effects of candesartan in patients treated with trastuzumab 95.…”
Section: Prevention and Treatment Of Cardiotoxicity Associated With Hmentioning
confidence: 85%
“…The PRADA (Prevention of Cardiac Dysfunction During Adjuvant Breast Cancer Therapy) trial tested whether angiotensin receptor blockers and/or beta‐blockers would be effective in preventing cardiotoxicity in patients diagnosed with breast cancer receiving anthracycline‐based chemotherapy with and without trastuzumab. The study showed modest benefit of candesartan, but not metoprolol, in preventing LVEF reduction assessed by magnetic resonance imaging94; however, neither medication was effective in preventing increases in high‐sensitivity troponin, a marker of subclinical myocardinal injury. A more‐recent randomized controlled trial failed to reproduce such beneficial effects of candesartan in patients treated with trastuzumab 95.…”
Section: Prevention and Treatment Of Cardiotoxicity Associated With Hmentioning
confidence: 85%
“…Kwestia, czy pacjenci z małym początkowym ryzykiem leczeni antracyklinami również odnoszą korzyści z profilaktycznego stosowania inhibitorów ACE, ARB lub beta-adrenolityków, pozostaje kontrowersyjna i obecnie nie można sformułować zalecenia na ten temat. W niedawno przeprowadzonej prospektywnej próbie klinicznej kontrolowanej placebo u chorych z wczesnym rakiem piersi leczonych antracyklinami stosowanie kandesartanu ograniczyło zmniejszenie LVEF w porównaniu z placebo lub beta-adrenolitykiem, natomiast nie miało wpływu na GLS ani biomarkery sercowe [227]. W tej próbie klinicznej metoprolol nie zapobiegł spadkowi LVEF związanemu z chemioterapią.…”
Section: Kobiety W Ciążyunclassified
“…Также есть сведения о при-менении в качестве кардиопротективных препаратов на фоне терапии антрацаклинами сартанов, статинов, антагонистов минералокортикоидных рецепторов, метформина [21]. В недавно завершившемся иссле-довании PRADA был продемонстрирован хороший кардиопротективный эффект кандесартана при его назначении онкологическим пациентам на фоне хи-миотерапевтического лечения [22]. Относительно ин-тервенционных методик имеются данные о том, что трансплантация сердца и ресинхронизирующая тера-пия при антрациклиновой кардиомиопатии не менее эффективны, чем при других неишемических кар-диомиопатиях [23,24].…”
Section: Ivabradin In Prevention Of Anthracycline Cardiotoxicityunclassified